Internally displaced children and HIV in situations of armed conflict in the DRC : a study of the obligations of the government and selected non-state actors - Nienaber, A.G. (Annelize Gertruida) (University of Pretoria, 2014)
Dissertation (LLM)--University of Pretoria, 2013.